Aspectos do desenvolvimento da experiência docente na educação superior: um estudo sob a ótica da teoria dos gêneros de atividade - Ecker, Daiana Aparecida Furlan (2016)
This analysis introduces results related to development of teaching experience from two professors of one Federal University who have taken part of one action of continued teacher training. We consider that the interplay among the individual, the language and the world cannot function straightly. It occurs through utterances, defined like real unit discursive communication, and genres of discourse (BAKHTIN, 1979/2011). Along the same line, the relation between the employee and his employment do not occur in a direct manner. This relationship takes place through genres of activity (CLOT, 2008/2010). As well as, a domain of speech genres has given possibility to individual an interaction with several discursive fields, a domain of activity genre allows the professional protruding in difficult situations traced in his employment. We know that the drafting for wield the teaching in the Tertiary Education is recommended by LDBEN (9394/96), which suggests that should be done in postgraduate program. In the mean time, what frequently happens an educational background based in a survey and not in the teaching. Thereby, several times we have observed difficulties in the accomplishment of teaching practice. Considering such aspects, this study seeks to comprehend the manner how the lecturers deal with the difficulties encountered in the classroom and how the years of experience have contributed or not for a domain of activity genre. In this regard, we have propped up in the development approach, introduced by Vigotsky, who asserts that the learning suitably organized results in development (VIGOTSKY, 1984/2007) and still explains the development of individual on the basis of relationship that it has with another, the social (VIGOTSKY, 1996b). For this purpose, were accomplished, by means of a snipped filmed lesson from each teacher, four sessions of self-confrontation (FAÏTA, 1996; CLOT, 2008/2010), two Simple and two Crusade, recorded in a visual format. This material was transcribed in accordance with standards from project NURC-SP (PRETI, 1999). For the analysis, we used three mains theories: of Linguistic, is mobilized the concept of speech genres (BAKHTIN) and all discursive topics (JUBRAN; FÁVERO); from Occupational Psychology, is utilized the activity genres (CLOT); from Psychology Historical-Cultural, is adopted the concept from Zone of Proximal Development and another/social in the development of individual (VIGOTSKY). In compliance with the study achieved, was possible to identify the aspects related to development of teaching experience of Tertiary Education. During the classes and reports of self-confrontation, we identify that both the professors, in the beginning of the career, they got more difficulties to deal with hindrances, and which now, with some years of experience, they get to domain better the difficult situations which they come across. They built up, for example, a greater facility in improvise examples in face of students’ difficulties in the comprehension of concepts. These aspects show that the professors have evolved the higher domain of genre, which allow them getting, in addition to turn the unexpected situation around that spring up in the professional context, as well know how to taking action in similar situation, which they have already run into in another moments. This domain enabled and enables the developing of the lecturers over the course of their professional performance.